Bioethical education on deliberation: the views of a novel - Araújo, Joana (2010)
Ethics is the study of the moral basis of human behavior that aims to determine the best course of action. Bioethics, as a transdisciplinary area, based both on ethics and on life sciences, reflects upon the ethical problems raised by new technologies and scientific research. One of the main tools to tackle bioethical problems is deliberation, a procedure that attempts to analyse problems, weighing up the principles and values involved as well as the context of each case. Due to the complexity of deliberation, educational projects should be promoted, providing the practice necessary for correct deliberation and raising awareness of the current ethical issues. It is our purpose to present a framework for ethical deliberation throughout the use of literature. Literary texts are essential, since they show human beings acting in space and time and they give the readers an opportunity to deliberate on ethical issues. Based on a literary text, we will reflect upon a controversial ethical issue - Preimplantion Genetic Diagnosis (PGD).